CHAPTER 7 STABILITY OF DETRITAL HEAVY MINERALS DURING BURIAL DIAGENESIS - Morton A.C.; Hallsworth C. (My University, 2007)
Detrital heavy-mineral assemblages respond to increasing burial diagenesis by progressive dissolution of unstable components. Case studies from sedimentary basins worldwide show a uniform pattern of relative stability. The order of stability during burial diagenesis is olivine (least stable) < orthopyroxene, clinopyroxene < sodic pyroxene < calcic amphibole, andalusite, sillimanite < epidote < titanite < kyanite < sodic amphibole < staurolite < allanite < garnet, chloritoid < tourmaline, monazite, spinel < rutile, anatase, brookite, zircon, apatite (most stable). Mineral dissolution can be recognised by corrosion textures on grain surfaces and by preservation of unstable minerals in low-porosity zones adjacent to friable sandstones with less diverse assemblages. Increasing pore fluid temperatures, accompanied by changes in pore fluid composition, are responsible for progressive mineral dissolution. There is, therefore, an indirect relationship between mineral diversity and burial depth in sedimentary basins worldwide. However, the depths at which individual minerals disappear vary markedly between basins, largely due to differences in pore fluid temperature gradients. Geological time is another significant factor in mineral depletion. Interpretation of provenance using heavy-mineral data from sandstones likely to have suffered burial diagenesis must carefully consider the possibility that some heavy-mineral species have been eliminated through dissolution. Evaluation of provenance under such circumstances must rely on parameters that are demonstrably unaffected by diagenesis. A combined approach, integrating provenance-sensitive ratio measurements with varietal data, either petrographic, geochemical or isotopic, is recommended. © 2007 Elsevier B.V. All rights reserved.
Keywords: CORROSION; DIAGENESIS; HEAVY MINERALS; PROVENANCE; STABILITY